Pengaruh Bimbingan Belajar Terhadap Prestasi Belajar Siswa Pondok Pesantren Madrasah Aliyah Al-Utrujiyyah Kota Karang Bandar Lampung - Thahir, Andi; Hidriyanti, Babay (Universitas Islam Negeri Raden Intan Lampung, 2014)
This study aims to determine and describe the effects of learning result from learning. To achieve these goals, the authors use quantitative methods with questionnaires and interviews. In the process of data analysis, this study used a simple regression analysis with. As the dependent variable. The result of this study is that learning has an influence on the improvement of student achievement.